Profile of Mathematics Education Students’ Understanding with Moderate Mathematics Ability in the Aspect of Dissection of Group - Jafar Jafar; I Ketut Budayasa; Dwi Juniati (STKIP Singkawang, 2018)
One aspect that can be used to identify the completeness of the students’ understanding to a concept is by doing dissection to the concept. This is a case study on the students of mathematics education who had moderate ability, and the objective was to obtain the profile of students’ understanding towards group concept on the aspect of dissection. The students’ understanding to the concept is needed very much to build foundation for understanding to other concepts in abstract algebra. Based on the result of the study, it was obtained that although the dominant elements that build the concept of group can be identified well but qualitatively the understanding of the students who have moderate ability in mathematics to the group concept is still weak. One of the causes is the mathematics logic as an instrument in managing information in group concept is not used accurately and tightly.